Pengaruh Penyuluhan Dalam Peningkatan Pengetahuan Kesehatan Reproduksi Remaja Pada Pengurus Pusat Informasi dan Konseling Mahasiswa UHAMKA - Nur Asiah (UHAMKA Press, 2016)
Counseling Impact on Increasing Adolescent Reproductive Health Knowledge of UHAMKA Student Counseling and Knowledge Center’s MemberIntroduction. Peer educator takes an important role considering most of adolescent getting reproductivehealth information from their peers. PIK M HERO is a group organized from, by and for undergraduatestudent in UHAMKA who has assignment to give an information and counseling regarding populationand family planning. To improve managerial aspect and services of PIK M HERO, it is necessary toconduct the training for PIK M HERO member. This study aimed to determine knowledge difference ofPIK M HERO member before and after education program. Methods. This study was analytic research using one group pretest-posttest design. The study began withfilling out the questionnaire (pretest), then researchers conducted education for respondents thenrespondents filled out the same questionnaire (posttest). The research was conducted on 25 students ofPIK M UHAMKA member whereas total sampling method has been used. Bivariate analysis wasconducted to determine the effect of health education on the level of respondent knowledge aboutreproductive health. Data were tested using paired t test and Wilcoxon test. Results. The average score knowledge of respondent before being given education is 66.4 which wascategorically 64% on the low score and 36% on the high score categoric. After given education, averagescore becomed 82,56 whereas categorically 68% has a high score categoric and 32% has a low scorecategoric. Statistic test show that there was a kwowledge score difference before and after giveneducation (p value = 0.001). Thus counseling was effective in gaining respondent knowledge aboutreproductive health.